EFL Students' Collaborative Writing Experiences in Hybrid Learning Environments - Khainur Jannah; Fathin Anajani Hilman (Prominent, 2026)
This study explores how EFL students at an Indonesian state polytechnic collaborated on a narrative writing task in a hybrid setting combining face-to-face classes with online work through Google Docs. Data collected included classroom observations over 12 sessions, analysis of three essay drafts, and semi-structured interviews with one lecturer and six students. The research focused on three questions: how students manage collaboration across physical and virtual environments, the challenges and opportunities of the hybrid format, and its impact on writing quality. Students frequently shifted between online and offline modes, using face-to-face discussions to clarify ambiguities in asynchronous comments. The hybrid approach facilitated interactions among students who rarely spoke together and provided lower-achieving students with feedback from more experienced peers. Peer trust varied, participation was inconsistent, and language barriers in commenting caused friction. Despite difficulties, an essay starting at a low level across all five writing aspects improved to an excellent level after two collaborative revisions. The results suggest that a hybrid collaborative model can enhance EFL writing skills, provided that offline support is thoughtfully designed alongside the online tools.